The Changing Antebellum Period through Early 20th Century Net Nutrition between Male and Females: A Difference-In-Decompositions within and across Group Comparison - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2021)
A population's average stature reflects cumulative net nutrition and changing long-run economic conditions facing women's economic opportunity, inequality, and net nutrition during development. This study uses stature as a measure for cumulative net nutrition to show how female and male statures varied around the US Civil War. Male statures and net nutrition decreased more than females with industrialization, indicating that women's net nutrition improved relative to men with emancipation and industrialization. The net nutrition of women in agricultural occupations was greater than women in other occupations; however, male stature returns associated with occupations increased more than women with the transition to free-labor.
Keywords: C10; C40; D10; I10; N30; 330; nutrition transition by gender; stature by gender; economic transitions